The effect of anti-alpha4 integrin antibody on brain lesion activity in MS. The UK Antegren Study Group. - Tubridy, N; Behan, P; Capildeo, R; Chaudhuri, A; Forbes, R; Hawkins, C; Hughes, R; Palace, J; Sharrack, B; Swingler, R; Young, C; Moseley, I; et al. (1999)
OBJECTIVE: To determine the effect of humanized monoclonal antibody against alpha4 integrin (reactive with alpha4beta1 integrin or very-late antigen-4) on MRI lesion activity in MS. METHODS: A randomized, double-blind, placebo-controlled trial in 72 patients with active relapsing-remitting and secondary progressive MS was performed. Each patient received two IV infusions of anti-alpha4 integrin antibody (natalizumab; Antegren) or placebo 4 weeks apart and was followed up for 24 weeks with serial MRI and clinical assessment. RESULTS: The treated group exhibited significantly fewer new active lesions (mean 1.8 versus 3.6 per patient) and new enhancing lesions (mean 1.6 versus 3.3 per patient) than the placebo group over the first 12 weeks. There was no significant difference in the number of new active or new enhancing lesions in the second 12 weeks of the study. The number of baseline-enhancing lesions (i.e., lesions that enhanced on the baseline scan) that continued to enhance 4 weeks following the first treatment was not significantly different between the two groups. The number of patients with acute MS exacerbations was not significantly different in the two groups during the first 12 weeks (9 in the treated group versus 10 in placebo) but was higher in the treatment group in the second 12 weeks (14 versus 3; p = 0.005). The study was not, however, designed to look definitively at the effect of treatment on relapse rate. Treatment was well tolerated. CONCLUSIONS: Short-term treatment with monoclonal antibody against alpha4 integrin results in a significant reduction in the number of new active lesions on MRI. Further studies will be required to determine the longer term effect of this treatment on MRI and clinical outcomes.